Catalytic Activity Origin and Design Principles of Graphitic Carbon Nitride Electrocatalysts for Hydrogen Evolution - Zhu, Yonghao; Zhang, Detao; Gong, Lele; Zhang, Lipeng; Xia, Zhenhai (Frontiers in Materials, 2019)
Graphitic carbon nitrogen (g-C3N4) has been shown a huge potential in photo-/electrocatalytic hydrogen generation owning to its unique electronic structure, high nitrogen content, excellent thermal and chemical stabilities. We have for the first time developed a descriptor and design principle to accurately predict the HER electrocatalytic activities of heteroatom-doped g-C3N4. The new descriptor includes the dopant and its bonding environmental information, which provides detailed guide to the rational design and screening of high-performance catalysts. A volcano relationship between the descriptor and the electrocatalytic activity was established, from which the most active dopant elements and related structures were identified. It was shown that doping near the edge of g-C3N4 could be a promising strategy in developing highly active metal-free g-C3N4-based catalysts. We also reveal the intrinsic origin of the catalytic activity of the doped g-C3N4 for different activity sites. Our work provides a basic design principle of heteroatom-doped g-C3N4 as an efficient HER catalyst and a fundamental understanding of the HER mechanism.